P-85 The relationships of eccentric and concentric isokinetic strength with sprinting speed in male sub-elite footballers. (18th November 2016) - Booysen, Marc Jon; West, Nastasha; Constantinou, Demitri
Abstract : Introduction: Sprinting in football matches contributes directly to securing ball possession and goal scoring (1). Research into physical qualities that underlie sprint performances is crucial. There is a strong relationship between strength and maximal sprinting speed in elite male footballers (2). However, it is uncertain whether these findings apply at sub-elite levels. Moreover, there is limited research investigating the relationships of concentric and more specifically eccentric strength with sprint performances. Therefore the aim was to determine the relationships of concentric and eccentric isokinetic strength with sprinting speed in male sub-elite footballers. Methods: Data was collected from preseason testing of 53 male footballers University (n = 32; age 20.8 ± 2.17 years) and semi-professional (n = 21; age = 23 ±3.22 years). The following tests were performed; 1.) Eccentric and concentric strength testing of the knee extensors and flexors at an isokinetic speed of 90 degrees per second and 2.) Linear sprints over 30 metres which included times for 10 metres (acceleration) and the flying 20 metre (maximal speed). Pearson product moment correlations were used to determine the relationships between isokinetic peak torque to body mass values (bilateral average) and sprinting times. Significance was set at P < 0.05. Results: A significant correlation was observed between eccentric strength of the knee flexors and the flying 20m sprint (r = −0.34; P = 0.02) (Table 1 ). Furthermore, concentric strength of the knee extensors and flexors were correlated with both 30m (r = −0.35, P = 0.02; r = −0.42, P = 0.002) and flying 20m sprints (r = −0.50, P = 0.0002; r = −0.52, P = 0.00007), respectively (Table 1 ). Conclusion: The results confirm the relationships of concentric (knee extensor/flexor) and eccentric (knee flexor) strength with maximal sprinting in male sub-elite footballers. However, the relationships are moderate, suggesting that other factors (neuromuscular and technical), may also play a role in determining sprint performances. The insignificant findings between strength and 10 metre sprints could be attributed to a smaller contribution of the knee extensor/flexor muscles to horizontal propulsion during accelerations. It is suggested that exercises that develop maximal concentric and eccentric strength be added to football-specific speed interventions in sub-elite footballers. Improving maximal strength in both contraction modes of the knee extensors and flexors may improve speed in sprints longer than 10m. References: Faude O, Koch T, Meyer T. Straight sprinting is the most frequent action in goal situations in professional soccer. Journal of Sports Sciences . 2012;30 (7):625–631 Cotte T, Chatard J-C. Isokinetic strength and sprint times in English Premier League football players. Biology in Sport . 2011;28 (2):89–94